Pharmacotherapeutic management of pediatric lymphoma - Mauz-Körholz, Christine; Ströter, Natascha; Baumann, Julia; Botzen, Ante; Körholz, Katharina; Körholz, Dieter (Pediatric drugs, 2018)
Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL) comprise approximately 15% of all childhood malignancies. Cure rates for both lymphoma entities have evolved tremendously during the last couple of decades, raising the 5-year survival rates to almost 100% for HL and to 85% for NHL. The mainstay therapy for both malignancies is still chemotherapy-with different regimens recommended for different types of disease. In HL, combined modality treatment, i.e., chemotherapy followed by radiotherapy, has long been the standard regimen. In order to reduce long-term side effects, such as second malignancies, most major pediatric HL consortia have studied response-based radiotherapy reduction strategies over the last 3 decades. For recurrent disease, high-dose chemotherapy followed by an autologous or an allogeneic hematopoietic stem-cell transplant is an option. No targeted agents have yet gained regulatory approval for use in pediatric patients with lymphoma. For adult lymphoma patients, the CD20 antibody rituximab and the CD30 antibody-drug conjugate brentuximab vedotin are targeted agents used regularly in first- and second-line treatment regimens. More recently, immune checkpoint inhibitors, phosphatidyl-inositol-3-kinase inhibitors, and Bruton's tyrosine kinase inhibitors appear to be very promising new treatment options in adult lymphoma. Here, we discuss the current experience with these types of agents in pediatric lymphoma patients.
First published: 10 November 2017
Gesehen am 23.03.2020